Adam Smith on Monopoly Theory. Making good a lacuna1. (6th March 2014) - Salvadori, Neri; Signorino, Rodolfo
Abstract This article analyses Adam Smith's views on monopoly by focusing on Book IV and V of The Wealth of Nations. It argues that the majority of scholars have assessed Smith's analysis of monopoly starting from premises different from those, actually though implicitly, used by Smith. We show that Smith makes use of the word 'monopoly' to refer to a heterogeneous collection of market outcomes, besides that of a single seller market, and that Smith's account of monopolists' behaviour is richer than that provided by later theorists. We also show that Smith was aware of the growth‐retarding effect of monopoly and urged State regulation.